Advancing managerial leadership development : philosophical, theoretical, and empirical insights from a humanistic adult learning perspective - Scholtz, Gert Jacobus (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.